2017
DOI: 10.1016/j.cub.2017.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Infrasonic and Ultrasonic Hearing Evolved after the Emergence of Modern Whales

Abstract: Mysticeti (baleen whales) and Odontoceti (toothed whales) today greatly differ in their hearing abilities: Mysticeti are presumed to be sensitive to infrasonic noises [1-3], whereas Odontoceti are sensitive to ultrasonic sounds [4-6]. Two competing hypotheses exist regarding the attainment of hearing abilities in modern whales: ancestral low-frequency sensitivity [7-13] or ancestral high-frequency sensitivity [14, 15]. The significance of these evolutionary scenarios is limited by the undersampling of both ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 43 publications
(112 reference statements)
3
59
1
Order By: Relevance
“…Therefore, within cetaceans, infrasonic hearing can be regarded as a purely mysticete trait, and ultrasonic hearing as an odontocete trait. Also, Mourlam and Orliac (2017) concluded that infrasonic and ultrasonic hearing evolved after the emergence of fully aquatic whales and within Neoceti, which contrasts with previous results of infrasonic sensitivity in basilosaurids (Ekdale, 2016;Park et al, 2017). However, no archaeocetes were included in our study, and a more detailed interpretation would be merely speculative based on our data.…”
Section: Occurrence Of Very Low-frequency and Infrasonic Hearingcontrasting
confidence: 54%
“…Therefore, within cetaceans, infrasonic hearing can be regarded as a purely mysticete trait, and ultrasonic hearing as an odontocete trait. Also, Mourlam and Orliac (2017) concluded that infrasonic and ultrasonic hearing evolved after the emergence of fully aquatic whales and within Neoceti, which contrasts with previous results of infrasonic sensitivity in basilosaurids (Ekdale, 2016;Park et al, 2017). However, no archaeocetes were included in our study, and a more detailed interpretation would be merely speculative based on our data.…”
Section: Occurrence Of Very Low-frequency and Infrasonic Hearingcontrasting
confidence: 54%
“…A. tarfa , like other protocetids, was considered able to hear high sonic frequencies, facilitating predation on sound‐producing fish (Bianucci & Gingerich, ; Fahlke et al. ), although a recent study based on the cochlear morphology questioned specialization for ultrasonic hearing among archaeocetes (Mourlam & Orliac, ).…”
Section: Discussionmentioning
confidence: 99%
“…; Racicot & Colbert, ; Ekdale & Racicot, ; Racicot et al. ; Mourlam & Orliac, ). Original CT data and 3D *.stl files of the endocasts will be made available through morphosource.org, those scanned at UTCT are available by request from UTCT and digimorph.org staff.…”
Section: Methodsmentioning
confidence: 98%
“…Two recent studies (Churchill et al. ; Mourlam & Orliac, ) have shown that nine measurements of the inner ear labyrinth in a variety of terrestrial, semi‐aquatic, and fully aquatic mammal groups correspond to hearing sensitivity, such that ultrasonic and infrasonic hearers show clear separation in a principal components analysis (PCA). To visualize the hearing ranges of our selected monodontid species alongside other artiodactyls, we built on these analyses by taking the same measurements as these previous authors, and added them to the PCA performed by Mourlam & Orliac ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation